2017
DOI: 10.1038/s41467-017-00241-z
|View full text |Cite
|
Sign up to set email alerts
|

Hole-phonon coupling effect on the band dispersion of organic molecular semiconductors

Abstract: The dynamic interaction between the traveling charges and the molecular vibrations is critical for the charge transport in organic semiconductors. However, a direct evidence of the expected impact of the charge-phonon coupling on the band dispersion of organic semiconductors is yet to be provided. Here, we report on the electronic properties of rubrene single crystal as investigated by angle resolved ultraviolet photoelectron spectroscopy. A gap opening and kink-like features in the rubrene electronic band dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…From this agreement and the theoretical result along the ΓR direction we can expect that m h * is largest (≈0.4 m 0 ) at the R point, although we could not directly measure the band dispersion at that point. It is necessary to highlight here that our results for the effective hole mass of CH 3 NH 3 PbI 3 single crystals via ARUPS measurements are larger than in inorganic semiconductor single crystals, such as silicon with m h * of 0.16 m 0 and GaAs with m h * of 0.076 m 0 , whereas they are much smaller than in organic semiconductor single crystals, such as Rubrene with m h * of >1.4 m 0 and pentacene with m h * = 3.43 m 0 . Furthermore, based on a broad band model (band width 0.26–0.55 eV in CH 3 NH 3 PbI 3 single crystals is much larger than k B T ), the drift mobility of a hole ( µ h ) can be estimated from the uncertainty principle using the following equation: μnormalh=eτm*>em*W20m0m*300T where τ is the relaxation time of the hole due to scattering, e is the elementary charge and T is the temperature.…”
Section: Summarized Parameters Of Various Experimental and Calculatedsupporting
confidence: 87%
“…From this agreement and the theoretical result along the ΓR direction we can expect that m h * is largest (≈0.4 m 0 ) at the R point, although we could not directly measure the band dispersion at that point. It is necessary to highlight here that our results for the effective hole mass of CH 3 NH 3 PbI 3 single crystals via ARUPS measurements are larger than in inorganic semiconductor single crystals, such as silicon with m h * of 0.16 m 0 and GaAs with m h * of 0.076 m 0 , whereas they are much smaller than in organic semiconductor single crystals, such as Rubrene with m h * of >1.4 m 0 and pentacene with m h * = 3.43 m 0 . Furthermore, based on a broad band model (band width 0.26–0.55 eV in CH 3 NH 3 PbI 3 single crystals is much larger than k B T ), the drift mobility of a hole ( µ h ) can be estimated from the uncertainty principle using the following equation: μnormalh=eτm*>em*W20m0m*300T where τ is the relaxation time of the hole due to scattering, e is the elementary charge and T is the temperature.…”
Section: Summarized Parameters Of Various Experimental and Calculatedsupporting
confidence: 87%
“…On a timescale shorter than the characteristic timescale for intermolecular vibrations, the charges are localized by the thermal disorder in the transfer integrals, but on longer timescales the charge carriers undergo diffusive motion driven by the waves of molecular lattice fluctuations, as depicted in Figure . The model is thus able to reconcile the experimental observation of concomitant delocalized and localized transport signatures . Within the relaxation time approximation (RTA), the instantaneous diffusivity ( D RTA , m 2 s −1 ) is expressed by Equation , where τ (s) is the characteristic time of a vibration mode of frequency ω (1/τ) and L τ (m) its related transient localization length (on the order of 2 nm for rubrene 3 , at room temperature) over which the localized charges undergo a diffusive transport (on a time scale shorter than τ).…”
Section: Charge Transportmentioning
confidence: 90%
“…A bandwidth of W ≈ 410––470 meV was recorded and transfer integrals, i.e., J a = −5 ± 3 meV, J b = 108 ± 4 meV, J d = 10 ± 15 meV were deduced ( Figure ). A direct evidence of the charge–phonon coupling in the bandwidth has recently been provided Kera et al who have experimentally observed a gap opening and kink‐like features in the electronic band dispersion of rubrene 3 . ARUPS is essentially a surface technique, whereas crystal structures are bulk properties.…”
Section: Charge Transportmentioning
confidence: 99%
“…The negative temperature dependence of mobility and Hall coefficient measurements have proved intermolecular charge coherence and band‐like transport in organic single crystals . The band dispersion of organic semiconductors has been directly characterized by angle‐resolved photoelectron spectroscopy, indicating that the vibronic coupling between electrons and molecular vibrations (or phonon) plays a significant role in the transition between hopping and band transports . The molecular vibrations can also be coupled to an optical mode in the infrared region not only under electronic excitation but also in the ground state.…”
Section: Introductionmentioning
confidence: 99%